(3ebGdI aj ESJNQGL JGQjN GdjghO hCYjGOges - (3CHh LYaQ Ydj Hf YHO Gddg Hf eMeO Hf eTGP GdbGjfjs
(3ChdgG (B:s
(3bGd CHh LYaQ Ydi Hf YHO Gddg Hf eMeO Hf HGeTGP GdbGjfi (B( (3EYde Cf Chd GdJSY YTQI Ydi MSGH GdjghO hCda heGjI hKeGfjI hCQHYjf ddCScfOQ aEPG CQOJ Cf JYde ai Ci SfI CfJ s
(3BNQgG (B:s
(3hYdi gPG GdeKGd jLQi GdYed hCf GdaSM dGjchf ai jhe GdCKfjf hGdCQHYGA hGdLeYI hdG jchf QCS GdSfI hGdMeO ddg QH GdYGdejf hGdUdGI Ydi fHjg eMeO hBdg s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3GdJGQjNs